2021
DOI: 10.5468/ogs.20094
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cysts disappear after 14-day oral regimen of Korean red ginseng extract in letrozole-induced polycystic ovarian syndrome

Abstract: Hormonal and inflammatory mechanisms are involved in the pathogenesis of polycystic ovarian syndrome (PCOS), which is a prevalent metabolic disorder among women of reproductive age. We aimed to evaluate the comparative efficiency of short-term oral administration of Korean red ginseng extract (KRGE) and the standard treatment on PCOS by focusing on the histopathological parameters and serum levels of luteinizing hormone (LH), folliclestimulating hormone (FSH), testosterone, and nuclear factor kappa B (NF-κB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In recent years, the incidence of PCOS has increased, resulting in higher disability-adjusted life-years [104]. There are different therapeutic approaches for management of PCOS [105][106][107]. The underlying pathophysiological mechanisms contributing to the development of PCOS are multifactorial; PCOS is more than one reproductive disorder [108].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of PCOS has increased, resulting in higher disability-adjusted life-years [104]. There are different therapeutic approaches for management of PCOS [105][106][107]. The underlying pathophysiological mechanisms contributing to the development of PCOS are multifactorial; PCOS is more than one reproductive disorder [108].…”
Section: Discussionmentioning
confidence: 99%
“…reported elevation of both numbers and size of primordial follicles in ovaries of three-month-old female rat infants born to diabetic mothers, which was treated with ginseng extract [ 22 ]. A recent study has reported the disappearance of ovarian cysts after a 14-day oral regimen of Korean red ginseng extract in an animal model [ 57 ]. Similarly, genistein, a phytoestrogen that binds to the ERs, protects ovarian follicles against radiotherapy and increases primordial, preantral, and antral follicles, and reduces atretic follicle counts through inhibition of apoptosis markers and upregulation of ERs in the ovary [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ginseng can protect gonadal function in hypothyroid female rat models; maintaining FSH, LH, and testosterone in the normal range [ 78 ]. Ginseng also protects ovarian follicles in letrozole-induced polycystic ovarian syndrome [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in aromatase activity, which is typically expressed in the ovary, could increase the intraovarian production of androgens, which simultaneously decreases estrogen levels, leading to the development of polycystic ovaries. The oral administration of letrozole to adult rats for at least 21 consecutive days induces acyclicity [ 21 ] and irregular estrus cycles [ 1 ]. Endocrine disturbances, including elevated LH and testosterone levels and decreased FSH levels reflecting the accumulation of endogenous ovarian androgen secretion, can be seen in this animal model, mimicking human PCOS.…”
Section: Discussionmentioning
confidence: 99%